PRESERVATION AND HARVEST OF BEET SEEDS IN THE WINTER VEGETATION PERIOD (World Economics and Finance Bulletin, 2022)
The article highlights the benefits of growing feeding beetroots without planting seedlings method over planting seedlings method, that this method reduces handwork labor by reduction of expenditures 2,5-3,0 times, increasing yield and quality of seeds and reduces opportunities for beet growing from 2 years to 9-10 months.
Keywords: With Seedlings; without seedlings; innovational technology; region